2001
DOI: 10.1554/0014-3820(2001)055[1408:reitng]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution in the Nebria Gregaria Group (Coleoptera: Carabidae) and the Paleogeography of the Queen Charlotte Islands

Abstract: Morphological differentiation in the ground beetles of the Nebria gregaria group, found on the Queen Charlotte Islands, has been used as support for the glacial refugium proposed for the northwest coast of North America. Two members of this species group, N. charlottae and N. louiseae, are restricted to cobble beaches in this archipelago. A third, N. haida, is found only in alpine regions of the archipelago and the adjacent mainland. The remaining two species of the gregaria group, N. lituyae and N. gregaria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Small refugial populations commonly show morphological differentiation due to random drift or directional selection while in isolation (e.g. Clarke et al. , 2001; Fedorov & Stenseth, 2001,2002).…”
Section: Discussionmentioning
confidence: 99%
“…Small refugial populations commonly show morphological differentiation due to random drift or directional selection while in isolation (e.g. Clarke et al. , 2001; Fedorov & Stenseth, 2001,2002).…”
Section: Discussionmentioning
confidence: 99%
“…The standard 2% is often considered a conservative estimate (see Arbogast & Slowinski 1998 and references therein), and published estimates for beetles range from ≈ 5–6% divergence per Myr for recent species (Juan et al . 1996; Clarke et al . 2001), through those around the standard 2% (Caccone & Sbordoni 2001; Farrell 2001; Barraclough & Vogler 2002), to about one‐third of this value (Gómez‐Zurita et al .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, analysis of fossil pollen data suggest that plant communities dramatically changed north of Vancouver Island at the LGM (Heusser 2000). Likewise, molecular phylogeographic studies of several northeastern Pacific terrestrial and anadromous taxa have shown both contrasting evidence of northern refugia (Byun et al 1997;Soltis et al 1997;Conroy and Cook 2000;Clarke et al 2001;Cook et al 2001;Ritland et al 2001;Smith et al 2001) and southward range contraction/expansion (Lance and Cook 1998;Stone et al 2002). While range shifts and extinction are likely related to abiotic factors (Jansson 2003), it is most plausible that the interplay between ecological, demographic, and abiotic factors plays a deterministic role in northern range limits.…”
Section: Paleo-sea Surface Temperatures and Coastal Glaciationsmentioning
confidence: 99%